Assessing the quality of studies in meta‐research: Review/guidelines on the most important quality assessment tools. (15th September 2020) - Luchini, Claudio; Veronese, Nicola; Nottegar, Alessia; Shin, Jae Il; Gentile, Giovanni; Granziol, Umberto; Soysal, Pinar; Alexinschi, Ovidiu; Smith, Lee; Solmi, Marco
Summary: Systematic reviews and meta‐analyses pool data from individual studies to generate a higher level of evidence to be evaluated by guidelines. These reviews ultimately guide clinicians and stakeholders in health‐related decisions. However, the informativeness and quality of evidence synthesis inherently depend on the quality of what has been pooled into meta‐research projects. Moreover, beyond the quality of included individual studies, only a methodologically correct process, in relation to systematic reviews and meta‐analyses themselves, can produce a reliable and valid evidence synthesis. Hence, quality of meta‐research projects also affects evidence synthesis reliability. In this overview, the authors provide a synthesis of advantages and disadvantages and main characteristics of some of the most frequently used tools to assess quality of individual studies, systematic reviews, and meta‐analyses. Specifically, the tools considered in this work are the Newcastle‐Ottawa scale (NOS) and the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) for observational studies, the Consolidated Standards of Reporting Trials (CONSORT), the Jadad scale, the Cochrane risk of bias tool 2 (RoB2) for randomized controlled trials, the Preferred Reporting Items for Systematic Reviews and Meta‐analysis (PRISMA) and the Assessment of Multiple Systematic Reviews 2 (AMSTAR2), and AMSTAR‐PLUS for meta‐analyses. What is already known?: The informativeness and quality of evidence synthesis inherently depend on the quality of what has been pooled into meta‐research projects. Beyond the quality of included individual studies, only a methodologically correct process, in relation to systematic reviews and meta‐analyses themselves, can produce a reliable and valid evidence synthesis. What is new?: In this overview, the authors provide a synthesis of advantages and disadvantages and main characteristics of some of the most frequently used tools to assess quality of individual studies, systematic reviews, and meta‐analyses. Potential impact: This overview serves as a starting point and a brief guide to identify and understand the main and most frequently used tools for assessing the quality of studies included in meta‐research. The authors here share their experience in publishing several meta‐research‐related articles covering different areas of medical sciences.